Screening and identification of microRNAs mediating cartilage endplate degeneration in human intervertebral disks - Jiang, Bei; Bai, Chong; Pan, Jie; Shen, Bin; Li, Lijun (Frontiers in Medicine, 2024)
Objective This study aimed to discover micro-ribonucleic acids (microRNAs) involved in the degeneration of cartilage endplates through next-generation sequencing and lay the foundation for further research. Methods The cartilage endplate was obtained from patients who underwent interbody fusion surgery at the Department of Spine Surgery, Shanghai East Hospital Affiliated to Tongji University, from 1 January 2020 to 1 January 2023. Total RNA was extracted from the cartilage endplate tissue. Discover differential genes through NGS. To annotate gene functions, all target genes were aligned against the Kyoto Encyclopedia of Genes (KEGG) and Gene Ontology (GO) databases. The GO enrichment and KEGG enrichment analyses of target genes were performed using phyper, a function of R. The p-value was corrected using the Bonferroni method, and a corrected p-value of ≤0.05 was taken as the threshold. GO terms or KEGG terms fulfilling this condition were defined as significantly enriched terms. The screened miRNAs and their target protein were verified in vitro using quantitative polymerase chain reaction (qPCR) and Western blotting (WB). Results RNA was extracted from normal and degenerated cartilage endplate tissues for NGS. Eight downregulated differentially expressed genes (DEGs) and 22 upregulated DEGs were found. The KEGG pathway analysis of these target genes revealed that differential microRNAs and target genes were enriched in different signaling pathways, and the regulated signaling pathways were mainly mitochondrial autophagy and autophagy. The qPCR results demonstrated a significant upregulation of miR-25-3p and miR-345-5p in degenerative cartilage endplate tissues (p ≤ 0.001). Western blot analysis revealed that BRD4 exhibited a marked increase in protein expression levels in degenerative cartilage endplate tissues (p ≤ 0.0001), while BECN1 showed a significant decrease in protein expression levels within these samples (p ≤ 0.0001). Conclusion We found that DEG hsa-miR-25-3p and hsa-miR-345-5p can be used as diagnostic and therapeutic targets for IDD. The significant target proteins of miR-25-3p and miR-345-5p were BRD4 and BECN1, respectively.